What can natural edges of gallery forests teach us about woody community performance in sharp ecotones?. (28th September 2016) - de Oliveira Coelho, Gabriela Aparecida; de Castro Nunes Santos Terra, Marcela; de Souza Almeida, Hisaias; van den Berg, Eduardo
Abstract: Aims: The diversity and structure of forest edges are a central issue in ecology. However, most studies have focused on anthropogenic forest edges, being natural ones least understood. We studied the communities of shrubs and trees in natural edges of gallery forests with the main goal of learning what are the main factors that shape the structure and diversity of these natural sharp ecotones. Methods: We evaluated 10 gallery forest sites, allocating in each of them three 15×20 m plots. The plots were laid out in relatively rectilinear stretches of forest edges, respecting a minimal distance of 10 m between each plot. As they are permanent plots and meant to study eventual fluctuations in the forest–grasslands limits, we allocated the plots with their longest side parallel to the forest edge and covering perpendicularly 5 m of the grassland and 10 m of forest. Inside the plots we identified, mapped and measured all shrub and tree individuals with diameter at breast height (DBH) ≥ 1cm. Important Findings: Although many differences exist among the communities in terms of density and basal area, all of them were highly dense and had relatively low basal areas. In addition, both the number of individuals and the basal area increased rapidly towards the forest interior. Our results also revealed that the edge communities are composed mainly by small individuals that demand a great amount of light. Both the vertical stratification and the proportion of the functional groups are similar among the sites yet change quickly in the first 10 m of the forest edge. However, the floristic similarities were low among the communities mainly due to the species turnover within each area. Therefore, although the overall structure is constant in the studied edges, the low floristic similarity among them possibly indicates that the species within the same functional groups are substituting each other across the sites. Despite older and seemingly stable, our results showed the gallery forest edges are quite similar to the anthropogenic edges or recent clearings. This points out that, independent of the age, those characteristics are possibly permanent in edges.